2018
DOI: 10.1186/s12913-018-3576-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Norwegian version of the hospital survey on patient safety culture in a prehospital environment

Abstract: BackgroundTo develop a culture of patient safety in a regime that strongly focuses on saving patients from emergencies may seem counter-intuitive and challenging. Little research exists on patient safety culture in the context of Emergency Medical Services (EMS), and the use of survey tools represents an appropriate approach to improve patient safety. Research indicates that safety climate studies may predict safety behavior and safety-related outcomes. In this study we apply the Norwegian versions of Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 57 publications
0
35
0
1
Order By: Relevance
“…Sorskar et al, [45] when applying HSOPSC in an emergency medical service, identified that the most fragile dimension was focused on the "hospital management support for patient safety" process, however, the dimension " non punitive response to error " showed a statistical correlation with the level of patient safety, proving to be an important factor to promote safe patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Sorskar et al, [45] when applying HSOPSC in an emergency medical service, identified that the most fragile dimension was focused on the "hospital management support for patient safety" process, however, the dimension " non punitive response to error " showed a statistical correlation with the level of patient safety, proving to be an important factor to promote safe patient care.…”
Section: Discussionmentioning
confidence: 99%
“…The Persian version of the hospital survey on patient safety culture (HSOPCS) was used to measure this variable in our study (Moghri et al, 2012). It is used worldwide as a valid and reliable tool for measuring the level of patient safety culture in hospitals (Sørskår, Abrahamsen, Olsen, Sollid, & Abrahamsen, 2018). The questionnaire has 42 items that measure the different dimensions of patient safety culture.…”
Section: Patient Safety Culturementioning
confidence: 99%
“…HEMS is a high-competence service and represents the sharp end in the prehospital chain [30]. The content of this paragraph is previously described in [28].…”
Section: Methodsmentioning
confidence: 99%
“…Although minor adjustments had to be implemented, and some items were pointed out as challenging in the prehospital context, no items were left out or conceptually changed before distribution of the survey. The HSOPSC-S items is retrieved from [28, 29], and minor adjustments and challenging items is thoroughly discussed in [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation